2016
DOI: 10.2351/1.4963270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric fields on tin nanoparticles prepared by laser ablation in water

Abstract: A pulsed laser beam from an excimer laser was used to ablate a solid tin target immersed in water in the presence of an external electric field. High fluence resulted in the formation of an overheated melt at the target surface resulting in homogeneous nucleation and phase explosion. The ablation products were studied with transmission electron microscopy. It was found that with no external field the size distribution of particles has peaks at ∼1 and ∼10 nm and that externally applied electric fields resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…They found that applying the electric field during laser ablation led to the increase of the Bi 2 O 3 particle size. Sapkota et al [ 135 ] used an excimer laser (351 nm) to ablate a solid tin target immersed in water in the presence of an external electric field, while Jumaa et al [ 136 ] reported the synthesis of gold NPs by the pulsed Nd:YAG (1064 nm) laser ablation in deionized water mainly to study the effect of the electric field on the antibacterial activity of these particles. Al-Haddad et al [ 137 ] synthesized Au NPs by pulsed laser (Nd:YAG, λ = 1064 nm), ablation of a gold target immersed in deionized water by 300 mJ of laser energy, while a DC electrical field was applied above the target with adjusted voltage.…”
Section: Lal Synthesis Methods: Principle Process Parameters and mentioning
confidence: 99%
“…They found that applying the electric field during laser ablation led to the increase of the Bi 2 O 3 particle size. Sapkota et al [ 135 ] used an excimer laser (351 nm) to ablate a solid tin target immersed in water in the presence of an external electric field, while Jumaa et al [ 136 ] reported the synthesis of gold NPs by the pulsed Nd:YAG (1064 nm) laser ablation in deionized water mainly to study the effect of the electric field on the antibacterial activity of these particles. Al-Haddad et al [ 137 ] synthesized Au NPs by pulsed laser (Nd:YAG, λ = 1064 nm), ablation of a gold target immersed in deionized water by 300 mJ of laser energy, while a DC electrical field was applied above the target with adjusted voltage.…”
Section: Lal Synthesis Methods: Principle Process Parameters and mentioning
confidence: 99%
“…The achieved average sizes were 11, 13, 17, 18, and 23 nm when the 0, 20, 30, 40, and 50 V/cm electric fields were applied, respectively. The increase of average size may be due to what happened in EFLAL process such as evolution of charge distribution, plume expansion, trapping electrons, and atom ionization which was reported bySapkota et al (2017).Since the plasma plume contains ions, free electrons, nanodroplets, and vapor, applied electric field affects electric charge distribution which decrease the rate of ion-electron recombination.Moreover, the enhancement of electric field increases the charge of nanodroplets and the rate of electrons trapped by them. According to…”
mentioning
confidence: 93%
“…PLAL is considered as a simple and low-cost technique that does not require any vacuum apparatus [6]. It could provide size-controlled nanoparticles without any chemical contamination [7].…”
Section: Introductionmentioning
confidence: 99%